Transformation of Social Capital in Urban Communities: A Study of Changing Interaction Patterns in the Digital Economy Era - Ahmad Mubarok (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
This study aims to analyze the transformation of social capital in urban communities as a result of the development of the digital economy and its implications for changing patterns of social interaction. The research background is based on the global shift towards a digital economy that not only affects the economic system but also the structure of social relations in urban communities. This study uses a qualitative approach with a case study design in an urban community with a high level of digital penetration. Data were collected through in-depth interviews, participant observation in physical and digital spaces, and documentation. Then, they were analyzed using an interactive model through data reduction, data presentation, and thematic conclusions. The results show a shift in interaction patterns from those based on geographical proximity to more flexible and functional digital networks. This transformation affects the forms of bonding, bridging, and linking social capital that now operate in a hybrid space between offline and online. Although the digital economy expands networks and opportunities for social participation, challenges such as shallow relationships, inequality in digital literacy, and the potential for social fragmentation remain. In conclusion, social capital is not experiencing a decline, but rather is undergoing a reconfiguration that requires adaptation and strengthening of digital literacy to maintain sustainable social cohesion in urban communities.